The effect of mobile-wallet service dimensions on customer satisfaction and loyalty: An empirical study - Ahmed S. Ajina; Jamal M. M. Joudeh; Nafez N. Ali; Ahmad M. Zamil; Tareq N. Hashem (Cogent Business & Management, 2023)
AbstractElectronic payment options have mostly superseded traditional cash payment methods. The growth of digital wallets, e-commerce, mobile payments, and other unusual payment methods has moved the global economy one step closer to a cashless society. Therefore, this study aims to understand how mobile-wallet service quality dimensions affect customer satisfaction and loyalty, as well as to explore users’ experiences with these wallets. The dimensions of the mobile wallet adopted were service quality, ease of use, usefulness, cost, and security. A quantitative approach was used, and a questionnaire was utilized and distributed based on a convenience sample of 557 respondents who were located in Jordan. The statistical techniques of AMOS and SPSS have been applied. The analysis results supported all the main hypotheses, arguing that mobile-wallet service quality leads to customer satisfaction and loyalty. Additionally, mobile wallet service dimensions have an impact on customer loyalty through customer satisfaction. Furthermore, it found that the perceived ease of use, perceived usefulness, and perceived security dimensions have no impact on customer satisfaction. Moreover, perceived ease of use and perceived security dimensions have no impact on customer loyalty. The study recommended the need for m-wallet providers to support m-wallets and other electronic services to enhance the possibility of good control over their technological tools to improve service quality, reduce costs, improve security, develop the relationship between the organization and its customers, and learn more about their desires and aspirations.